Causes of Formation of Syndrome of Emotional Cold - Aslanyan, T. S. (Psychological Prospects Journal, 2011)
The article is devoted to the analazis of formation of syndrome of emotional cold, obstructing establishing the intimacy between partners. Among the main causes considered basic and structural blemish, earlier injurys.